Pharmacotherapies for Posttraumatic Stress Disorder: A Meta-Analysis. Issue 5 (May 2016) - Gu, Wenjie; Wang, Chao; Li, Zuofeng; Wang, Zhen; Zhang, Xiaoyan
Abstract : Abstract: The purpose of this study was to assess the acceptability and efficacy of all types of pharmacotherapeutic agents in reducing the symptoms of posttraumatic stress disorder (PTSD). In this systematic meta-analysis, the dropout and response rates of various pharmacotherapy and placebo treatments reported by randomized clinical trials were compared. A total of 34 reports that described the acceptability and efficacy of PTSD pharmacotherapies were retrieved and analyzed. Of them, 30 trials examined the dropout rate as an index of acceptability and revealed the superiority of the PTSD pharmacotherapy to placebos (odds ratio, 0.75; 95% confidence interval, 0.66–0.86; n = 4313). The response rate was determined in 20 trials as an index of efficacy, showing that the PTSD pharmacotherapies were superior to the placebos (odds ratio, 1.47; 95% confidence interval, 1.34–1.62; n = 2166). Pharmacotherapy is an important component of the care of patients with PTSD.